Diseño de políticas contables del “sindicato unitario nacional de trabajadores” subdirectiva Boyacá (2022)
The present investigation is carried out with the purpose of elaborating a proposal for the design of an accounting policies manual in the "SUNET" Organization Subdirective Boyacá, which will serve as a guide for an adequate financial management of the organization and to achieve the transition to the new IFRS regulations - SMEs in Colombia. For the development of the study, a descriptive qualitative approach was used; starting with a diagnosis of the financial information and its economic facts during a period to establish specific facts through a DOFA matrix, and then, based on the International Financial Reporting Standards (IFRS for SMEs), the proposal for the design is prepared. of an Accounting Policies Manual.